BAHASA KASAR DALAM BAHASA SAKAI DI KECAMATAN MINAS KABUPATEN SIAK - Kurniati, Siti; Sinaga, Mangatur; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study examines the use of abusive language in the Sakai language in Minas District, Siak Regency. The technique of collecting data is done by interviewing, recording, and recording the utterances spoken by the informant. Data were analyzed to describe crude language in the form, form, reference, and use. In this study the rough language in the Sakai language used by the Minas community in the form of forms is divided into words, phrases, and clauses. Based on rough language references in the Sakai language, Minas Subdistrict is distinguished by circumstances, animals, objects, body parts, spirits, and activities.Key Words: Abusive language, form, reference, situation.